Synbiotics Supplements Lower the Risk of Hand, Foot, and Mouth Disease in Children, Potentially by Providing Resistance to Gut Microbiota Dysbiosis - Guo, Xiaoying; Lan, Zixin; Wen, Yaling; Zheng, Chanjiao; Rong, Zuhua; Liu, Tao; Chen, Siyi; Yang, Xingfen; Zheng, Huimin; Wu, Wei (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Hand, foot and mouth disease (HFMD) is an acute enterovirus-induced disease. Gut microbiota dysbiosis has been identified as a factor that plays an important role in enteral virus infection, but the gut microbiota profile in hand, foot and mouth disease has rarely been studied in a large population. Methods: A total of 749 children were recruited from hospitals and communities in the period from May to July 2017. Clinical and anthropic information was collected by trained personnel using a survey, and fecal samples were collected and processed for 16S sequencing. Results: We observed a significant alteration in the microbiota profile of children with hand, foot and mouth disease compared with that of control children. We found that Prevotella and Streptococcus were enriched in children with hand, foot and mouth disease, whereas beneficial bacteria, including Bifidobacterium and Faecalibacterium, were depleted. By employing a logistic model, we observed that children with hand, foot and mouth disease who were administered a combination of probiotics and prebiotics exhibited reduced morbidity, and their gut microbiota showed potential resistance to the dysbiosis detected in hand, foot and mouth disease. Conclusions: This study suggested that the gut microbiota of patients with hand, foot and mouth disease exhibits dysbiosis and that a combination of probiotics and prebiotics supplements potentially helps maintain the homeostasis of the gut flora.